A cost‐effective strategy for the synthesis of polystyrene‐polyisobutylene‐polystyrene triblock copolymer (SIBS) based on dicumyl chloride/TiCl4/Ti(OiPr)4 initiating system. Issue 8 (12th January 2023) - Xu, Shucheng; Yang, Ke; Liu, Qiang; Li, Hui; Zhang, Hao; Zhuang, Tao; Yan, Shouke; Ding, Junwei
Abstract: A cost‐effective strategy has been developed for the synthesis of polystyrene‐polyisobutylene‐polystyrene (PS‐PIB‐PS) triblock copolymer (SIBS) with relative narrow molecular weight distribution (MWD) via the addition of Ti(O i Pr)4 . First, the controlled polymerization of styrene (St) was achieved by using TMPCl/TiCl4 /Ti(O i Pr)4 initiating system from −80 to −50°C in a cost‐effective solvent mixture n‐Hexane/CH2 Cl2 (v/v = 6/4). The –O i Pr group was present in the form TiCl3 (O i Pr) for TiCl4 /Ti(O i Pr)4 ratio more than 3/1 and moderated the lifetime of the growing PS cation. Subsequently, Ti(O i Pr)4 was added to the living charge of PIB initiated by initiator 1, 4‐dicumyl chloride (DCC), followed by the addition of styrene monomer. The success of this developed synthesis methodology was confirmed by comparing the findings from GPC (Gel permeation chromatography) traces with and without the addition of Ti(O i Pr)4 . SIBS with nearly 30% weight content of PS (SIBS30) was successfully obtained with an optimally narrow MWD of 1.49 at −80°C by employing the TiCl4 /Ti(O i Pr)4 ratio of 6/1. Interestingly, SIBS30 with a very narrow PDI of 1.22 could be successfully synthetized at an elevated temperature of −60°C. Abstract :